DERAJAT DISMENORE PADA MAHASISWI DIII KEPERAWATAN YANG MENGALAMI OBESITAS DI POLITEKNIK NEGERI MADURA - Elisa Christiana; Nindawi Nindawi; Yulia Riskina Mufida (Universitas Islam Madura, 2023)
Dysmenorrhea is a condition that is detrimental to young women because it has a big impact on health, young women with obesity is one of the high factors that will experience dysmenorrhea. The purpose of this study was to find out how the degree of Dysmenorrhea in Obese Adolescent Girls Student Health Department Diploma III Nursing Study Program Madura State Polytechnic. Method: This study uses a descriptive design. The population and sample were all obese young women, students of the Health Department of the DIII Nursing Study Program, Madura State Polytechnic, with a total population of 18 respondents, using total sampling technique. Data collection used the Numerical Rating Scale (NRS) which included back pain, breast pain and lower abdominal pain. The research data were processed (editing, coding, scoring, tabulating and interpreting) and analyzed descriptively (percentage). Results are presented in tables and narrated. Results: The results of this study showed that the majority of respondents with a degree of dysmenorrhea had a moderate category of 12 respondents (67%) in young women who were obese female students of the DIII Nursing Study Program, Madura State Polytechnic. Conclusion: The degree of dysmenorrhea, which is in the moderate category, for female students improves their coping mechanisms with relaxation and endurance exercises, so that the pain becomes lighter. Health workers including nurses periodically provide education that dysmenorrhea can be felt depending on many factors, but the most important thing is physical and psychological health.